REGIONAL POLICY OF THE EU AND UKRAINE UNDER THE DEEPENING CONTRADICTIONS OF GLOBALIZATION - Melnyk, Alla; Adamyk, Victoria (Journal of European Economy, 2017)
The problem of the EU regional policy modernization under the conditions of globalization processes activation is studied. The influence of global factors and changes in the EU regional policy is determined produced on the transformation of the regional policy in Ukraine. In the context of the development of the Ukraine’s regional policy the problems are defined of economic development and welfare of the citizens in the regions of Ukraine, also the areas of cooperation between Ukraine and the EU are outlined.